Early school leaving in rural areas of Europe and Spain - Santamaría Luna, Rogeli (Avances en Supervisión Educativa, 2015)
The rural environment has changed and is changing. The diversity of definitions of rural and applied methods difficult to compare data and research on the rural. So the invisibility of rural education is promoted and it is unclear whether rural improvement in educational indicators.There are some socio-economic conditions that appear to influence educational outcomes and in turn the educational level of the community influences the development of it. Early school leaving (ESL) is one of the key indicators of education in Europe. In rural areas ESL is typically higher.In this short article will present data and sources, but above all be evident that the low presence of rural factor in education and that the rural / urban divide still exists. Referencians Europe cited Spain and the start of the indicators of quality of life and early school leaving is estimated in Spain, rural or not, 2020 in relation to the proposed European Territorial Agenda 2020 target of 15%. Besides conclusions and proposals to be referred.
Keywords: early school leaving (ESL); rural education invisibility